Nociceptive Sensitizers Are Regulated in Damaged Joint Tissues, Including Articular Cartilage, When Osteoarthritic Mice Display Pain Behavior. Issue 4 (April 2016) - Driscoll, Clare; Chanalaris, Anastasios; Knights, Chancie; Ismail, Heba; Sacitharan, Pradeep K.; Gentry, Clive; Bevan, Stuart; Vincent, Tonia L.
Abstract : Objective: Pain is the most common symptom of osteoarthritis (OA), yet where it originates in the joint and how it is driven are unknown. The aim of this study was to identify pain‐sensitizing molecules that are regulated in the joint when mice subjected to surgical joint destabilization develop OA‐related pain behavior, the tissues in which these molecules are being regulated, and the factors that control their regulation. Methods: Ten‐week‐old mice underwent sham surgery, partial meniscectomy, or surgical destabilization of the medial meniscus (DMM). Pain‐related behavior as determined by a variety of methods (testing of responses to von Frey filaments, cold plate testing for cold sensitivity, analgesiometry, incapacitance testing, and forced flexion testing) was assessed weekly. Once pain‐related behavior was established, RNA was extracted from either whole joints or microdissected tissue samples (articular cartilage, meniscus, and bone). Reverse transcription–polymerase chain reaction analysis was performed to analyze the expression of 54 genes known to regulate pain sensitization. Cartilage injury assays were performed using avulsed immature hips from wild‐type or genetically modified mice or by explanting articular cartilage from porcine joints preinjected with pharmacologic inhibitors. Levels of nerve growth factor (NGF) protein were measured by enzyme‐linked immunosorbent assay. Results: Mice developed pain‐related behavior 8 weeks after undergoing partial meniscectomy or 12 weeks after undergoing DMM. NGF, bradykinin receptors B1 and B2, tachykinin, and tachykinin receptor 1 were significantly regulated in the joints of mice displaying pain‐related behavior. Little regulation of inflammatory cytokines, leukocyte activation markers, or chemokines was observed. When tissue samples from articular cartilage, meniscus, and bone were analyzed separately, NGF was consistently regulated in the articular cartilage. The other pain sensitizers were also largely regulated in the articular cartilage, although there were some differences between the 2 models. NGF and tachykinin were strongly regulated by simple mechanical injury of cartilage in vitro in a transforming growth factor β–activated kinase 1–, fibroblast growth factor 2–, and Src kinase–dependent manner. Conclusion: Damaged joint tissues produce proalgesic molecules, including NGF, in murine OA.